ڕۆڵی ژن لەبواری پزیشکی لەسەردەمی پێغەمبەر (صل ﷲ علیە وسلم) (توێژینەوەی هەڵێنجراو) - رحیم, حسین محمد صالح; قادر, دنیا صلاح (Sulaimani Journal for Humanities, 2023)
This research talks about the role of women in the field of medicine in the time of the Prophet (peace and blessings of Allaah be upon him) in the arabs before the coming of the holy religion of Isalim. Medical works were common among the priests, magicians, and diviners. Each tribe had its own diviner to treat the disease, but when the sun of Isalim raised, medical science was given more importance, as it was an important aspect of human being's life. Humanity, education and research in the field of medicine has seen more progress, the Prophet (peace be upon him) , he always encouraged medical studies. he encouraged colleagues to go to the doctors and treat themselves. Of course, women had an active role in the field of medicine alongside men and were trying to examine and research in the field. women have been experts in many medical fields such as: mixing many different types of drugs - surgery - eye diseases - skin diseases - pregnant women's care during the birth of the baby. women have participated in several wars with the Muslim army and treated wounds. The aim of the research is to determine the role of Muslim women in the time of the Prophet (peace and blessings of Allaah be upon him) In the field of medicine which is an important and bright part in Islamic civilization and explaining the work.women had done in the field of medicine in which they were experts.